"Inter Alia: Aliens and AI". (1st June 2019) - Raley, Rita; Samolsky, Russell
Contemporary anxiety concerning our efforts to communicate with aliens might be understood in terms of the exponential advances in neural network research (so-termed "Artificial Intelligence") and the probability that the aliens we encounter are more likely to be alien AIs than organic beings. The premise of our paper is that the disquieting sense that AI possesses, or is possessed of, an external intelligence, one that operates autonomously, unpredictably, and, in our deepest fears, mutinously, is projectively displaced onto extra-planetary aliens. Our paper offers an analysis of Trevor Paglen's satellite work, The Last Pictures, as well as Eduardo Kac's Inner Telescope and Lagoogleglyph series. We conclude with a speculative imagining of an AI-archaeologist encountering in the distant future the orbital ring of dead satellites, one of which contains Paglen's curated image archive.